Genetic tests as the strongest motivator of cooperation between participants and biobanks–Findings from cross-sectional study - Majchrowska, Anita; Pawlikowski, Jakub; Sak, Jarosław; Świerczyńska, Blanka; Suchodolska, Magdalena (Frontiers in Genetics, 2024)
The development of the scientific potential linked with biobanking and research on human biological material is highly dependent on the willingness of potential donors to cooperate with entities that collect the material. For this reason, it is crucial to identify the circumstances and factors that may encourage potential participants to donate their biological material. In particular, knowledge of the motivational factors that can be modified by the persons managing a biobank may prove notably important for shaping the organizational and communication policy of the biobank and other scientific institutions.The research was carried out on a group of 1100 people over 18 years of age representing the adult population of Poland in 2021.Results: More than half of the respondents declared their willingness to donate a blood sample for research purposes to a biobank (57.8%). The most often indicated incentives among the factors supporting the donation of biological material were offers of: obtaining the results of genetic tests predicting the risk of diseases (77.1%), blood tests (71.3%), the possibility of obtaining a small remuneration (64.6%) and the carrying out of genetic ancestry tests (60.4%).Offering the possibility of performing additional diagnostic tests, especially genetic tests, may significantly increase the willingness of potential donors to cooperate with biobanks and other entities collecting human biological material for the purpose of scientific research. However, attention should also be paid to the challenges and risks linked with respecting the privacy and autonomy of research participants.